Exome sequencing and in vitro studies identified podocalyxin as a candidate gene for focal and segmental glomerulosclerosis - Barua, Moumita (2013)
Our understanding of focal and segmental glomerulosclerosis (FSGS) has advanced significantly from the studies of rare, monogenic forms of the disease. These studies have demonstrated the critical roles of multiple aspects of podocyte function in maintaining glomerular function. A substantial body of research has suggested that the integral membrane protein podocalyxin (PODXL) is required for proper function of podocytes, possibly by preserving the patency of the slit diaphragm by negative charge-based repulsion. Exome sequencing of affected cousins from an autosomal dominant pedigree with FSGS identified a co-segregating private variant, PODXL p.L442R, affecting the transmembrane region of the protein. Of the remaining 11 shared gene variants, two segregated with disease but their gene products were not detected in the glomerulus. In comparison to wild type, this disease-segregating PODXL variant facilitated dimerization. By contrast, this change does not alter protein stability, extracellular domain glycosylation, cell surface expression, global subcellular localization, or interaction with its intracellular binding partner ezrin. Thus, a variant form of PODXL remains the most likely candidate causing FSGS in one family with autosomal dominant inheritance, but its full effect on protein function remains unknown. Our work highlights the challenge faced in the clinical interpretation of whole exome data for small pedigrees with autosomal dominant diseases.